2014
DOI: 10.1155/2014/387215
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Effect of 405 nm Monochromatic Laser on Endodontopathogenic Microorganisms

Abstract: The purpose of this study is to evaluate the usefulness of 405 nm monochromatic laser irradiation as an alternative management for prevention and/or treatment of endodontic infections. A monochromatic laser-emitting device equipped with a 405-nm laser diode was developed. Using this device, the effect of 405 nm laser irradiation on the growth of Porphyromonas gingivalis, Prevotella intermedia, Enterococcus faecalis, and Candida albicans, which are microorganisms associated with persistent endodontic infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
3
7
0
2
Order By: Relevance
“…Other studies also reported that visible light is effective against Porphyromonas gingivalis, Fusobacterium nucleatum, Staphylococcus aureus, Streptococcus mutans, and Escherichia coli [28,29]. The results of our previous study also confirmed that the irradiation with a 405 nm blue-violet laser had a bactericidal effect against P. gingivalis which is a major periodontopathogenic microorganism as well as Prevotella intermedia, and even against Candida albicans which is a major responsible fungus causing candidiasis [30]. These results demonstrate the possibility that the irradiation with a 405 nm blue-violet laser is capable of eliminating a variety of microorganisms adhered to the surface of osteosynthetic materials and preventing effectively the delayed postoperative infection.…”
Section: Introductionsupporting
confidence: 83%
“…Other studies also reported that visible light is effective against Porphyromonas gingivalis, Fusobacterium nucleatum, Staphylococcus aureus, Streptococcus mutans, and Escherichia coli [28,29]. The results of our previous study also confirmed that the irradiation with a 405 nm blue-violet laser had a bactericidal effect against P. gingivalis which is a major periodontopathogenic microorganism as well as Prevotella intermedia, and even against Candida albicans which is a major responsible fungus causing candidiasis [30]. These results demonstrate the possibility that the irradiation with a 405 nm blue-violet laser is capable of eliminating a variety of microorganisms adhered to the surface of osteosynthetic materials and preventing effectively the delayed postoperative infection.…”
Section: Introductionsupporting
confidence: 83%
“…33 In addition to safety, the tasks of laser destruction or inactivation of biological objects, such as pathogenic microorganisms, 34 cancer cells, 35 etc., have been discussed. The safety limit of light exposure becomes important in the study of living cells.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action in this case is still unknown. However, it is known that the use of blue light with the objective of evaluating fungal load in in vitro studies and bacterial load in humans has also obtained effective results, with significant reduction of microorganisms 5,9,13 .…”
Section: Discussionmentioning
confidence: 99%
“…When these come into contact with blue light, generate singlet oxygen and other reactive oxygen species, leading to cell death 13 . Inamura et al (2014) evaluated the effects of 405 nm blue light on pathogenic microorganisms present in the oral cavity, among them C. albicans, demonstrating a 90% reduction in fungal load when using a dose of 240J for 20 minutes 13 . This study justifies the use in the vaginal mucosa because of the similar tissue characteristics14.…”
Section: Discussionmentioning
confidence: 99%